Measuring Developer Work to Support the Software Project Manager: An Exploratory Study - Ferreira, Matheus Silva; Martins, Luana Almeida; Júnior, Paulo Afonso Parreira; Costa, Heitor Augustus Xavier (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
Software project management is an essential practice to achieve the goal of success in these projects and a challenging task for the Project Manager (PM). Therefore, information about developers' work can be valuable in supporting PM. Several studies have addressed this topic and suggested different strategies for obtaining such information. Given the variety of existing strategies, the need arises to know the state of the art regarding the theme. In this paper, what relevant information for PM and how that information can support the project management practices are presented, especially regarding risk management and people management. So, an exploratory study was performed applying Systematic Mapping of Literature technique. Contributions include the identification of 58 metrics, 4 sources of information, and 7 PM's activities supported by the measurement of developer work. In addition, aspects to be explored on the subject are presented, inspiring new studies in the field of Software Engineering.